Meningkatkan Kemampuan Menyimak Anak Usia 4-5 Tahun melalui Metode Bercerita dengan Menggunakan Media Boneka Tangan - Vynna Pramestiani; Ine Nirmala; Nida'ul Munafiah (Syntax Corporation Indonesia, 2024)
This study aims to improve the listening ability of children aged 4-5 years through the application of storytelling methods using hand puppet media. The research method used in this study is an experimental method with pre-test and post-test designs. The subjects of the study were children aged 4-5 years in a randomly selected kindergarten. The results showed an increase in children's learning outcomes on the themes of My Environment, My Needs, animals through the method of telling stories using hand puppets. This can be known the results of the child's listening ability before using the storytelling method. Thus, the average increase in the level of success of children's listening ability results after applying the storytelling method using hand puppets.